Total and Regional Body Composition of NCAA Division I Collegiate Basketball Athletes - Raymond-Pope, Christiana J.; Solfest, Anna L.; Carbuhn, Aaron; Stanforth, Philip R.; Oliver, Jonathan; Bach, Christopher W.; Bosch, Tyler; Dengel, Donald R. (International Journal of Sports Medicine, 2020)
This study aimed to examine body composition using dual X-ray absorptiometry (DXA) in male and female NCAA Division I collegiate basketball athletes. Two-hundred ten (male [M]/female [F]=88/122) basketball athletes’ total and regional fat mass, lean mass, bone mineral density, and visceral adipose tissue were measured. Athletes were classified as: point guards (M/F=27/34), shooting guards (M/F=18/27), small forwards (M/F=13/18), power forwards (M/F=21/27), and centers (M/F=9/16). ANOVA and Tukey’s HSD assessed positional differences by sex. In males, centers and power forwards had greater total fat mass (p<0.025), lean mass (p≤0.001), and visceral adipose tissue (p<0.001) than other positions. Male centers had greater arm and leg fat mass and lean mass than point guards, shooting guards, and small forwards (p≤0.049), and greater arm bone mineral density than point guards (p=0.015). In females, centers had greater total fat mass (p<0.001) vs. other positions and greater total lean mass, arm fat and lean masses, arm and leg bone mineral density, and visceral adipose tissue vs. point guards and shooting guards (p≤0.005). Female point guards had lower total bone mineral density than power forwards (p=0.008). In conclusion, these sex- and position-specific total and regional body composition measurements in collegiate basketball players provide population-specific normative data.
Keywords: dual X-ray absorptiometry (DXA); bone mineral density; fat mass; lean mass, visceral adipose tissue